Autism genetic testing information needs among parents of affected children: A qualitative study. Issue 6 (June 2016) - Li, Ming; Amuta, Ann; Xu, Lei; Dhar, Shweta U.; Talwar, Divya; Jung, Eunju; Chen, Lei-Shih
Highlights: We found parents expressed an interest to learn about autism genetic testing. Parents' preferred topics about autism genetic testing included cost and benefits. Parents' most desired delivery method for learning was Web-based education. Developing educational materials based on our findings is needed. Abstract: Objective: Leading health agencies recommend physicians to provide information regarding genetic testing for autism spectrum disorders (ASD) to parents of affected children. How to effectively provide this information, however, is unclear for physicians. This qualitative study examined the information needs regarding ASD genetic testing among parents of affected children. Methods: Semi-structured, in-depth interviews were conducted with 42 parents who had at least one child with ASD. Content analysis was utilized to analyze the interview data. Results: The majority of parents (83%) reported they had never received information regarding ASD genetic testing from their doctors. Nevertheless, most parents (86%) expressed an interest to learn about this information. Their preferred topics included: cost (60%), benefits (48%), accuracy (38%), test procedure (29%), potential physical harms from the test (29%), confidentiality (12%), previous utilization by other affected families (2%), and eligibility criteria for this genetic testing (2%). Moreover, parents mentioned various methods to facilitate their learning, including Web-based approaches (43%), workshops/seminars (36%), brochures and flyers (31%), and videos (10%). Conclusion: To promote parental informed decision-making regarding ASD genetic testing, educational materials should be developed based on our findings. Practice implications: Application of these needs assessment findings will subsequently improve the delivery of healthcare services.